Desain Program Pembelajaran Inovatif untuk Meningkatkan Minat Siswa Terhadap Ilmu Al-Qur'an - Hasan Badri; Merlyn Ika Rosyida Putri; Hennira Rohyatin; Ilzam Hubby Dzikrillah Alfani; Aji Rizqi Ramadhan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This study aims to design an innovative learning program that can increase students' interest in the science of the Qur'an. In today's digital era, the challenge of attracting students' attention to religious material is increasing. Therefore, a creative and interactive approach is needed in the learning process. The program designed integrates information technology, active learning methods, and content that is relevant to students' daily lives. Through the use of digital media such as learning applications, interactive videos, and online discussion platforms, it is hoped that students can be more involved and motivated to study the science of the Qur'an. This study uses a qualitative method with a case study approach in several educational institutions. The results of the study showed a significant increase in student interest after the implementation of this program, as well as positive feedback from teachers and parents. These findings are expected to be a reference for the development of a more interesting and effective Islamic religious education curriculum in the future.